Field‐Effect Transistors: Wafer‐Scale Synthesis of Reliable High‐Mobility Molybdenum Disulfide Thin Films via Inhibitor‐Utilizing Atomic Layer Deposition (Adv. Mater. 47/2017). Issue 47 (14th December 2017) - Jeon, Woojin; Cho, Yeonchoo; Jo, Sanghyun; Ahn, Ji‐Hoon; Jeong, Seong‐Jun
Abstract : A reliable and rapid manufacturing process of 2D semiconductor material remains a fundamental challenge toward its successful incorporation in high‐performance nanoelectronics. In article number1703031, Ji‐Hoon Ahn, Seong‐Jun Jeong, and co‐workers introduce inhibitor‐utilizing atomic layer deposition (iALD) as a noval method to meet these requirements on a wafer‐scale. They successfully demonstrate highly crystalline few‐layered iALD‐MoS2 thin films with excellent mobility (11.8 cm 2 V −1 s −1 ) and on/off ratios (>10 8 ) as the channel material in field‐effect transistors on a 6″ wafer.